Using technology to enhance clinical supervision - Renfro-Michel, Edina Lynn, 1970-; Rousmaniere, Tony (Alexandria, VA : American Counseling Association, 2016)
This book is the first comprehensive research and practice-based guide for understanding and assessing supervision technology and for using it to improve the breadth and depth of services offered to supervisees and clients.
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Counselors -- Supervision of; Counseling -- Technological innovations; Counseling -- organization & administration; Organization and Administration; Technology -- trends; Diffusion of Innovation; Electronic books